Uniportal video assisted thoracic surgery: hilar dissection - Solli, Piergiorgio; Bertolaccini, Luca; Lacava, Nicola; Parri, Sergio Forti; Kawamukai, Kenji; Bonfanti, Barbara; Pardolesi, Alessandro (Video-Assisted Thoracic Surgery, 2017)
In recent years, the uniportal approach has become one of the most exciting and innovative developments in minimally invasive thoracic surgery. While the debate over its supposed advantages, learning curve and complexity continues, this manuscript explores the technical aspects of performing the hilar dissection for a lobectomy via the uniportal approach. Using a step-by-step narration, surgical details and key tips and tricks are laid out for the beginner hoping to clarify basic steps of the technique.